A Biomechanical Study on Failed Snatch Based on the Human and Bar Combination Barycenter. (10th May 2022) - Liu, Gongju; Zhu, Houwei; Ma, Jing; Pan, Huiju; Pan, Xu; Zhang, Yingyue; Hu, Ting; Fekete, Gusztáv; Guo, Haiying; Liang, Minjun
Abstract : Objective . The purpose of this research was to use a new method the human and bar combination barycenter to exposit the differences between successful and failed characteristics of snatch attempts in competition. Try to establish an effective biomechanical method that can uncover the main factors for the failed snatch. The obtained results will provide valuable information for weightlifters to improve the success rate in snatch by altering their technical issues accordingly. Methods . A 3-D video analysis method was used to compare the characteristics of the heaviest successful and failed attempts of ten elite weightlifters in the men's 73 kg category. The video was captured under competitive conditions at the 2019 World Weightlifting Championships, the 2019 Asian Weightlifting Championships, and the 2020 China Olympic Trial. The video data were digitized using the SIMI°Motion7.50 3-D system (Germany). Results . Significant difference (P > 0.05 ) was not found between the successful and failed attempts in the parameters, such as the maximal vertical rising velocity, the maximal vertical height, and the vertical displacement of the barbell. The maximal descending acceleration of the human body, the time duration, the angles of the hip, and knee joints were no significant difference. However, significant differences were found in the variation of the human and bar combination barycenter on the X - axis in the inertial ascent stage and the squat support stage (t = 2.862, P < 0.05 ; t = 3.376, P < 0.05 ). Conclusions . A probable cause of the failed snatch is that the displacement of human and bar combination barycenter on the X - axis is not enough to reach the position for supporting barbell during the inertial ascent stage and the squat support stage. The reason is that the strength of reclining of torso at the end of the force phase is insufficient. Insufficient knee flexion in the knee flexion phase (M 2 ), which leads to a lower maximum vertical velocity of barbell, may be an indirect factor leading to the failed snatch. The cumulative variation of human and bar combination barycenter on the X - axis can effectively determine the technical characteristics between the success and failure in snatch.